Dose- and substrate-dependent reduction of enteric methane and ammonia by natural additives in vitro - Battelli, Marco; Nielsen, Mette Olaf; Nørskov, Natalja P. (Frontiers in Veterinary Science, 2023)
Ruminants contribute to global warming by emitting greenhouse gasses, particularly methane (CH4) which is a product of rumen fermentation. The use of feed additives able to modulate rumen fermentation is a promising strategy to reduce enteric CH4 and ammonia (NH3) emissions. Among the various strategies investigated, plant secondary metabolites (PSMs) have attracted attention due to their apparent potential to reduce enteric CH4 and NH3 emissions, and it would be possible to use such compounds as feed additives in organic production systems. In an in vitro system simulating rumen fermentation, we have tested the impact of different classes of naturally occurring PSMs; catechin and quercetin (flavonoids), salicylic acid (phenolic acid) and tannic acid (hydrolysable tannin). The PSMs were added to two different basal feeds (maize and grass silages) at three inclusion doses 1.5, 3 and 6% of the feed dry matter (DM). CH4 production was significantly lowered upon addition of quercetin to two basal feeds at doses of 3% and 6%, and this without changes in concentrations of total volatile fatty acid (VFA) produced during fermentation. Quercetin, as the only tested additive, reduced CH4 production, and when added to maize silage and grass silage, the reduction increased linearly with increasing dose, ie., by 51% and 43%, respectively, at a dose of 3% of feed DM and by 86% and 58%, respectively, at a dose of 6% of feed DM. Moreover, quercetin significantly reduced NH3 concentration by >12% at doses of 3% and 6% in feed DM irrespective of the basal feed used as compared to when the basal feeds were incubated alone. Although none of the other additives affected CH4 formation, several additives had significant impacts on concentrations of NH3 and VFAs in the incubated fluid after fermentation. This study demonstrated a dose-dependent ability of quercetin to reduce CH4 emission from rumen fermentation, however, the magnitude of the suppression of CH4 depended on the basal feed. Furthermore, quercetin reduced NH3 concentration irrespective of the basal feed type. These findings encourage to in vivo studies to verify whether quercetin can reduce CH4 emission also in cows.